DÉTERMINISME GÉNÉTIQUE DES CARACTÈRES MORPHO-PHYSIOLOGIQUES LIÉS AU RENDEMENT CHEZ LE BLÉ DUR EN ZONE SEMI-ARIDE DES HAUTS PLATEAUX SÉTIFIENS, ALGÉRIE - Sofia, Hamli; Hamenna, Bouzerzour; Amar, Benmahammed; Abdelmalek, Oulmi; Kenza, Kadi; Dalila, Addad (European Scientific Journal, ESJ, 2015)
The present investigation was undertaken to study the inheritance pattern of morpho-physiological traits: relative water content, excised leaf water loss, flag leaf area and membrane stability, in an F3 population of durum wheat (Triticum durum Desf.). The results reflected a satisfactory range of variability in the evaluated traits. Range magnitude of the four traits represented the equivalent of 5.0 to 11.4 times the least significant difference at 5% level. Transgressors with variable frequency were observed for all the measured traits. In fact 25% of the F3 lines showed a relative water content greater than 85%, 3% has a flag leaf area superior to 26 cm², 8% had a low leaf water loss rate and 11% expressed a low electrolyte leakage rate, suggesting a high membrane stability. Medium to high broad sense heritability estimates were noted for the measured traits. Medium to high genetic gain expressed as percent of the base population mean was observed, taking the following values: 11.0%, 24.0%, 68% and 88%, for relative water content, flag leaf area, excised leaf water loss rate, and percent of cell injury, respectively. Altogether, the obtained results indicated that the studied cross population would be of interest in the breeding program and an effective progress can be made through selection of these morpho-physiological characters to enhance stress tolerance and grain yield potential.